Biological, phytochemical and molecular docking characteristics of Laurus nobilis L. fresh leaves essential oil from Palestine - Nidal Jaradat; Mohammed Hawash; Mohammed T. Qaoud; Nawaf Al-Maharik; Mohammad Qadi; Fatimah Hussein; Linda Issa; Ahmad Saleh; Laith Saleh; Ahmad Jadallah (BMC, 2024)
Abstract Background The historical use of Laurus nobilis L., the plant is native to the Mediterranean region and has been cultivated for its aromatic leaves, which are used as a flavoring agent in cooking and for their potential therapeutic properties. Methods The purpose of the current investigation was to characterize the essential oil composition of the fresh L. nobilis leaves from Palestine by using the gas chromatography-mass spectrometry (GC-MS) technique. DPPH (2,2-diphenyl-1-picrylhydrazyl), p-nitrophenyl butyrate, and 3,5-dinitro salicylic acid (DNSA) methods were employed to estimate the antioxidant, antiobesity, and antidiabetic effects of the essential oil. While MTS assay were used to evaluate their antiproliferative activities on panels of cell lines. Moreover, the docking studies were aided by the Prime MM GBSA method for estimating binding affinities. Results The GC-MS investigation demonstrated that the fresh L. nobilis leaves essential oil has a variety of chemicals, about 31 different biochemicals were identified, and the major compounds were 1,8-cineole (48.54 ± 0.91%), terpinyl acetate (13.46 ± 0.34%), and α-terpinyl (3.84 ± 0.35%). Furthermore, the investigated oil demonstrated broad-spectrum antimicrobial activity against all tested bacterial and candidal strains and significantly inhibited the growth of MCF-7 cancerous cells more than the chemotherapeutic drug Doxorubicin. Furthermore, it contains robust DPPH free radicals, as well as porcine pancreatic α-amylase and lipase enzymes. Using the 1,8-cineole compound as the predominant biomolecule found in the L. nobilis essential oil, molecular docking studies were performed to confirm these observed fabulous results. The molecular docking simulations proposed that these recorded biological activities almost emanated from its high ability to form strong and effective hydrophobic interactions, this led to the getting of optimal fitting and interaction patterns within the binding sites of the applied crystallographic protein targets. Conclusion The results of these experiments showed that the fresh L. nobilis leaves essential oil has outstanding pharmacological capabilities, making this oil a potential source of natural medications.